Editorial - Buran, Sümeyra; Dedeoglu, Cagdas (Journal of Posthumanism, 2021)
Welcome to the second issue of the Journal of Posthumanism, which presents four articles, two commentaries, one book review, and two artistic works. It is also our pleasure to host the special issue entitled â€œThe KJSNA Conference Session on Philosophical Posthumanismâ€ that has five commentaries.